Widespread Environmental Presence of Multidrug-Resistant Salmonella in an Equine Veterinary Hospital That Received Local and International Horses - Soza-Ossandón, Paula; Rivera, Dácil; Tardone, Rodolfo; Riquelme-Neira, Roberto; García, Patricia; Hamilton-West, Christopher; Adell, Aiko D.; González-Rocha, Gerardo; Moreno-Switt, Andrea I. (Frontiers in Veterinary Science, 2020)
Salmonella enterica is a highly infectious microorganism responsible for many outbreaks reported in equine hospitals. Outbreaks are characterized by high morbidity and mortality rates, nosocomial transmission to other patients, zoonotic transmission to hospital personnel, and even closure of facilities. In this study, 545 samples (environmental and hospitalized patients) were monthly collected during a one-year period from human and animal contact surfaces in an equine hospital that received local and international horses. A total of 22 isolates were obtained from human contact surfaces (e.g., offices, pharmacy) and animal contact surfaces (e.g., stalls, surgery room, waterers), and one isolate from a horse. Molecular serotyping revealed 18 isolates as S. Typhimurium and three as S. Infantis. Nineteen isolates were resistant to at least one antimicrobial class, and only two isolates were susceptible to all antimicrobials tested. In addition, we identified nine multidrug-resistant (MDR) isolates in S. Typhimurium, which displayed resistance to up to eight antimicrobials (i.e., amoxicillin/clavulanate, ampicillin, ciprofloxacin, chloramphenicol, streptomycin, gentamicin, trimethoprim/sulfamethoxazole, and tetracycline). Pulsed-Field Gel Electrophoresis revealed the presence of three PFGE patterns permanently present in the environment of the hospital during our study. The persistent environmental presence of MDR Salmonella isolates, along with the fact that local and international horses are attended in this hospital, highlights the importance of improving biosecurity programs to prevent disease in horses and the hospital personnel and also for the global dissemination and acquisition of MDR Salmonella.